Estudio de la relación entre trastornos de personalidad y recaída en pacientes drogodependientes que han formado parte del proceso de internamiento en la unidad de C.I.T.A.B.M. (Centro Integral de Tratamiento de Adicciones Benito Menni) perteneciente al Instituto Psiquiátrico Sagrado Corazón. - Pasquel Andrade, Erika Gabriela (2013)
This work was performed in order to delve into the topic of addiction, from its multiple causes, with reference to patients who have been in the process of internment at the Center for Addiction Treatment Comprehensive Benito Menni, Sacred Psychiatric Institute Heart. Consider emerging questioning the relationship that could have the Substance Use Disorders and Personality Disorders and its relationship to relapse. For this, it was necessary to delve into the subject of addiction, relapse and treatment (mainly Therapeutics Community) and personality disorders, reviewing literature and other sources related information sources.